Bony Incarceration of the Extensor Pollicis Longus Tendon Mimicking Rupture - Barrera, Janos; Ryu, Jessica; Yao, Jeffrey (Journal of Wrist Surgery, 2019)
Background Distal radius fractures are a relatively common injury, and rupture of the extensor pollicis longus (EPL) has been known to occur in a small number of nondisplaced distal radius fractures. In contrast, bony incarceration of the EPL tendon is an exceedingly rare occurrence and warrants special attention.Case Description Here we present a case of bony incarceration of the EPL tendon following distal radius fracture that mimicked tendon rupture. Following EPL release, the patient had improved function and pain in the wrist.Literature Review We identified three case reports of EPL tendon entrapment following distal radius fracture, and compared and contrasted the clinical features of tendon rupture versus bony entrapment.Clinical Relevance Our results suggest that both the type of fracture (displaced vs. nondisplaced) and the chronicity of symptoms may provide important diagnostic clues for the hand surgeon managing distal radius fracture patients presenting with EPL dysfunction.
Keywords: distal radius fracture; tendon entrapment; tendon rupture; wrist fracture